Magnetic Vortex States in Small Octahedral Particles of Intermediate Titanomagnetite - E. Khakhalova; B. M. Moskowitz; W. Williams; A. R. Biedermann; P. Solheid (Geochemistry, Geophysics, Geosystems)
Abstract Fine particles of titanomagnetites (Fe3‐xTixO4, x > 0.5) in the pseudo‐single‐domain (PSD) size (0.5–20 μm) are important carriers of natural remanent magnetization in basalts. Understanding the mechanism of magnetic recording in these grains has important implications for paleomagnetic studies. This study reports first observations of magnetic vortex states in intermediate titanomagnetite. We imaged magnetic structures of 109 synthetic titanomagnetite grains with x = 0.54 (TM54) and 1–4‐μm size using magnetic force microscopy. For six grains, we explored local energy minimum states after alternating field demagnetization and saturation isothermal remanent magnetization. According to the magnetic force microscopy results, 80% of TM54 grains display in‐plane magnetization with one to four domains, vortex‐like or flux‐closure structures, and Néel‐like domain walls. Electron backscatter diffraction data on six grains showed that their surface orientations are cutting planes of octahedral crystals and those with approximately square cross sections are within 15° of a (100) crystallographic plane. Magnetic force microscopy observations of magnetic structures in ~1.5‐μm grains agree well with numerical micromagnetic modeling of a pyramidal shaped grain with a (100) square base and displayed four discrete local energy minimum states: a single vortex as a ground state and three multivortex states with higher energy. Our observations show that vortex states in titanomagnetite grains (1–5 μm) occur at the lower end of the PSD size range in this mineral and corresponding to a size range known to carry stable and reliable remanence in natural titanomagnetites.